Inequality in Immunization 2023 - Hosseinpoor, Ahmad Reza; Danovaro, M. Carolina; Nambiar, Devaki; Wallace, Aaron; Johnson, Hope (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Global immunization rates were stagnating prior to the COVID-19 pandemic, and declined further in 2020 and 2021, with substantial variation. Across countries, the level of protection afforded by immunization varies, with many countries reporting gaps in coverage of Human Papilloma Virus (HPV) and seasonal influenza, and many population subgroups, especially children, being left behind. In this Special Issue, we explore the latest evidence on various types of immunization across the life course at global, regional, national, and subnational levels. Exploring various dimensions of inequality-such as economic status, subnational geographic regions, sex, maternal education-and other categories, this issue includes contributions characterizing the situation of inequality, the drivers of inequality, and finally, actions and initiatives that hold promise for enhancing equity of immunization across countries.